A Study of a Review of Internal Control Systems In Light of Ethical Behaviors of The Banking Service Provider - Diana Neamah Abdulrazzaq Al-Khazraji; Muaamal Hussein Jwesim; Ghufran shallal mohammed (Peerian Journals Publishing, 2024)
The purpose of the current study is to identify a comprehensive review of the role of internal control systems in light of the ethical behaviors of banking service providers, as it is noted in recent times that most institutions suffer from undesirable behaviors that directly or indirectly affect the evaluation of their performance, which motivated the current study to study these behaviors by identifying the shortcomings suffered by institutions and working to benefit from the Accordingly, the current study contributed to presenting a set of studies and working to discuss them in a manner commensurate with the reality of the banking sector in Iraq and providing a set of results that keep pace with the reality of service providers in the banking sector, and proposing a set of recommendations that can contribute to addressing undesirable ethical practices that can To affect the evaluation of the performance of these banks in one way or another, hence the current study came out with a set of results, foremost of which was that the banking sector in Iraq suffers from weakness in internal control systems, which directly affected the ethical behaviors of service providers, which means that the absence of effective internal control procedures and independence affected the performance of internal control, which encouraged the spread of corruption and nepotism practices among workers.
Keywords: control system; internal control systems